Therapeutic effect of intense pulsed light on different types of chalazion in children - Jiao Jiang; Xiaoge Yang; Feifan Du; Wei Zheng; Yang Yang (Scientific Reports, 2024)
Abstract This study aims to investigate the effectiveness of Intense Pulsed Light (IPL) therapy for chalazion treatment while also exploring potential variations in sensitivity among different types of chalazion. A total of 149 patients were selected to receive tobramycin combined with IPL treatment and tobramycin combined with hot compress. The treatment groups were divided into cystic type and granulomatous type according to different clinical manifestations. The course of treatment was 3 weeks. The improvement was based on the ultrasound measurement of the masses reduction of more than 50% or disappearance. In the IPL group, 17 (22.67%) cases were cured, 39 (52.00%) were effective, and 19 (25.33%) were ineffective. This includes: cystic type was cured in 3 (15.79%), effective in 5 (26.32%) cases, ineffective in 11 (57.89%) cases; granulomatous type was cured in 14 (25.00%) cases, effective in 34 (60.71%) cases, ineffective in 8 (14.29%) cases. In the hot compress group, 5 (6.76%) cases were cured, 16 (21.62%) cases were effective and 53 (71.62%) cases were ineffective. The cystic type was cured in 2 (8.00%) cases, effective in 3 (12.00%) cases and ineffective in 20 (80.00%) cases; the granulomatous type was cured in 3 (6.12%) cases, effective in 13 (26.53%) cases and ineffective in 33 (67.35%) cases. The cure rate and efficacy rate of IPL treatment is higher than that of hot compress treatment, the treatment effect of IPL treatment on granulomatous chalazion is better than that on cystic type.